Optimalisasi Tata Kelola Arsip Perangkat Nagari untuk Pelayanan Publik di Maninjau Kabupaten Agam, Sumatra Barat - Nelisa, Malta; Hayati, Yenni; Rasyid, Yulianti; Nabila, Jeihan (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
Nagari Maninjau in Agam Regency, West Sumatra is one of the popular tourist areas that are not only known by the local community, but also by domestic and foreign tourists. This condition causes many administrative matters to be managed by the Village-chief office of Maninjau. So far, archive management has been carried out in a simple manner according to the knowledge possessed by the nagari apparatus and has not been in accordance with archive governance standards. This paper aims to describe efforts to optimize archive management through writing official letters, using archive classification schemes, organizing and filing archives, using Archives Retention Schedules, and using electronic archive management applications. The method used is training and guidance by involving all Nagari apparatus in Nagari Maninjau. The results of this activity are: (1) increasing the understanding of the nagari apparatus on the administration of official texts and direct implementation of the documents produced after the activity; (2) increased understanding of the use of archive classification schemes and implementation of the arrangement and filing of archives according to standards; (3) increased understanding of the use of the archive retention schedule; and (4) implementation of the use of electronic records management applications.